Sonodynamic therapy on chemically induced mammary tumor : Pharmacokinetics, tissue distribution and sonodynamically induced antitumor effect of porfimer sodium - Yumita, Nagahiko; Okuyama, Nobuo; Sasaki, Kazuaki; Umemura, Shin‐ichiro (Cancer science, 2004)
The sonodynamically induced antitumor effect of porfimer sodium (PF) was evaluated on a chemically induced mammary tumor in Sprague‐Dawley rats. The timing of 24 h after the administration of PF was chosen for the ultrasonic exposure, based on pharmacokinetic analysis of the PF concentrations in the tumor, plasma, skin and muscle. At a PF dose not less than 2.5 mg/kg and at a free‐field ultrasonic intensity not less than 3 W/cm2, the synergistic effect between PF administration and ultrasonic exposure on the tumor growth inhibition was significant. The ultrasonic intensity showed a relatively sharp threshold for the synergistic antitumor effect, which is typical of an ultrasonic effect mediated by acoustic cavitation. These results suggest that PF is a potentially useful as a sonosensitizer for sonodynamic treatment of chemically induced tumors.